Influence of single nucleotide polymorphisms (SNPs) in immunoregulatory genes in the morbidity of preterm newborns - Andrade Ramos, Bruna Ribeiro de [UNESP]; Cosi Bento, Giovana Fernanda [UNESP]; Navascues Bernardino, Romulo Augusto [UNESP]; Miot, Helio Amante [UNESP]; Silva, Marcia Guimaraes [UNESP] (Taylor & Francis Ltd, 2019)
Background: Prematurity is the main cause of perinatal and neonatal morbidity and mortality worldwide. Single nucleotide polymorphisms (SNPs) have been associated with the pathogenesis of morbidities in preterm neonates. We aimed to investigate the association between SNPs in regulatory genes of innate immune response IL1B, IL6, IL6R, IL10, TNFA, TNFRII, TLR2 and TLR4 and neonatal/infant morbidities in preterm newborns. Methods: Oral swabs were collected from 272 newborns (91 preterm and 181 at term) seen at Botucatu Medical School, Unesp, between 2013 and 2014 and SNPs were identified using Taqman Genotyping Assays. Medical records were examined to obtain data regarding neonatal/infant morbidity. Stepwise binomial logistic regression models were used to explain the morbidities. Results: Minor neonatal morbidity was influenced by the clinical parameters of maternal age and newborn weight at birth and by the presence of the allele IL6R2 C (rs2228145) while major neonatal morbidity was only influenced by gestational age. Minor infant morbidity was associated with the allele TLR2 T (rs4696480) and major infant morbidity was associated with gestational age and presence of IL6R2 C. Conclusion: The presence of SNPs that exacerbate the inflammatory response increases the susceptibility to neonatal and infant morbidity.
Keywords: Infant morbidity; innate immunity genes; neonatal morbidity; prematurity; single nucleotide polymorphisms